Use of Biologics in Inflammatory Bowel Disease: Combination and Sequential Therapy - Putra Nur Hidayat; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2022)
Inflammatory bowel disease (IBD) in the form of ulcerative colitis (UC) and Crohn's disease (CD) has multifactorial etiology and multiple inflammatory pathways. Newer treatments with biologic agents are used as an adjunct to conventional therapy. Biological agents such as anti-TNF, anti-integrin, and anti-interleukin are believed to be able to overcome the inflammation that underlies the occurrence of IBD. The “step up” approach in IBD therapy uses conventional drugs with low potency but fewer side effects as the first line, followed by biologic agents as second line therapy. However, the result is often a delay in the management of severe complications of IBD. A “top down” approach is currently being used to successfully prevent severe complications of IBD by using biologic agents early. Biological agent therapy can be initiated in moderate to severe IBD either in combination or sequentially. But in the end, various parameters must be considered before starting the use of biologic agents such as drug effectiveness, safety profile, drug availability, price, and patient preferences.